Designing Product-Service System Framework - Teppola, Tuukka (My University, 2021)
Multiple previous studies have focused on either PSS innovation or Design Thinking, but none have examined the combination of PSS fundamentals and Design Thinking methodology. As a result, the thesis's objective is to develop a framework for PSS innovation that is iterative in na-ture and customer-centric. CompanyCo, a electronics manufacturing company, is used as a case company for this study. The thesis aims to develop a process for the Product-Service System (PSS) innovation that supports CompanyCo's strengths, capabilities, and strategy. First, this study demonstrated through a case study in district heating that an appropriate PSS innovation framework for CompanyCo's emerging offering could be based on The New Double Diamond Model of Design Thinking, the Design Thinking macro process, and PSS fundamentals. The framework is divided into "finding the right problem," which defines the problem, and "find-ing the right solution," which drafts the solution via PSS essentials and rapid prototyping. Secondly, the thesis explores CompanyCo’s capabilities and pitfalls towards servitisation as de-scriptive "current state study.” Questionnaire were conducted for this study: an online form. The study aims to understand the organisation's current situation and help it become a more agile PSS provider. A single company was studied using multi-method qualitative and quantitative re-search. The findings indicate that the strengths to leverage in servitisation are CompanyCo's dedicated people and their enthusiasm for driving a cross-organisational development strategy and PSS's. CompanyCo's product portfolio is well-positioned towards servitisation due to its end-to-end capabilities, scientific innovation, and value-adding products that include a tangible component of value. Study subject’s hardware portfolio represents an opportunity to capitalize on potential value-added pricing and value communication opportunities. Pitfalls to servitisation include CompanyCo's unclear processes for customer information, daily customer information flow, and transparency of the service offering's cost structure. Consistency in PSS solutions, marketing, producing, and selling customised bundles are significant challenges. The findings suggest that hardware manufacturing traditions continue to haunt the transition, manifesting themselves in the company's tooling and processes. The result covers only a minority of the company’s em-ployees, and only one framework is used. This can bias the results. The thesis shows that the designed PSS innovation framework could be used for PSS innovation in the case company. The research company solely determines the theoretical framework's ap-plicability. The framework could have been tested on multiple companies. Case studies are highly subjective, allowing for researcher and interpreter errors. The thesis took a specific approach (iterative, customer-centric procedures) rather than considering alternative viewpoints.
Keywords: innovations; product development; district heating; prototypes; processes; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics